A combined experimental and micromechanical approach to investigating PTC and NTC effects in CNT-polypropylene composites under a self-heating condition. (1st June 2022) - Kil, Taegeon; Jin, D.W.; Yang, Beomjoo; Lee, H.K.
Abstract: The present study proposed a combined experimental and micromechanical approach to investigating positive temperature coefficient (PTC) and negative temperature coefficient (NTC) effects in carbon nanotube (CNT)-polypropylene composites under a self-heating condition. The electrical and heating performance of the composites were investigated by electrical conductivity measurements and self-heating tests with various input voltages. The test results showed that composites with a CNT content of 5.0 wt.% exhibited excessive heat generation, showing a transition of the PTC effect to the NTC effect. Moreover, a micromechanical modeling was proposed to predict the occurrence of the PTC and NTC effects in the composites, considering various distances between CNTs and wavinesses of CNT. The change of the distance between CNTs under a heating condition was estimated, using the molecular dynamics software Material studio. Comparisons between the predictions and the experimental results were made to show the applicability of the proposed modeling scheme.